Factors that enable effective One Health collaborations - A scoping review of the literature. - Kaylee Myhre Errecaborde; Katelyn Wuebbolt Macy; Amy Pekol; Sol Perez; Mary Katherine O'Brien; Ian Allen; Francesca Contadini; Julia Yeri Lee; Elizabeth Mumford; Jeff B Bender; Katharine Pelican (PLoS ONE)
Advocates for a One Health approach recognize that global health challenges require multidisciplinary collaborative efforts. While past publications have looked at interdisciplinary competency training for collaboration, few have identified the factors and conditions that enable operational One Health. Through a scoping review of the literature, a multidisciplinary team of researchers analyzed peer-reviewed publications describing multisectoral collaborations around infectious disease-related health events. The review identified 12 factors that support successful One Health collaborations and a coordinated response to health events across three levels: two individual factors (education & training and prior experience & existing relationships), four organizational factors (organizational structures, culture, human resources and, communication), and six network factors (network structures, relationships, leadership, management, available & accessible resources, political environment). The researchers also identified the stage of collaboration during which these factors were most critical, further organizing into starting condition or process-based factors. The research found that publications on multisectoral collaboration for health events do not uniformly report on successes or challenges of collaboration and rarely identify outputs or outcomes of the collaborative process. This paper proposes a common language and framework to enable more uniform reporting, implementation, and evaluation of future One Health collaborations.